THE IMPACT OF INFLATION EXPECTATIONS ON HOUSEHOLD WELL-BEING: AN EMPIRICAL ANALYSIS - Katarína Ilenčíková; Patrícia Krupová (Trendy v podnikání)
For decades, understanding financial and subjective well-being has been central to research, given its relevance to individual quality of life and policy decisions (Helliwell et al., 2019; Brüggen et al., 2017). Both financial freedom and self-reported happiness are essential aspects of well-being, which are influenced significantly by inflation, including past experiences, current levels, and future expectations (Cupak & Siranova, 2023; Dolan et al., 2009; Coibon et al., 2019). The literature, however, presents mixed results: while some studies suggest that inflation negatively impacts well-being (Prati, 2023), others suggest a more positive relationship (Golem et al., 2010). This paper investigates the link between inflation expectations and well-being from the household perspective, addressing a notable gap in the research, particularly relevant during periods of high inflation and economic instability. Using HFCS data from 2021—a year marked by the COVID-19 pandemic and heightened economic uncertainty—this study examines household perceptions of price dynamics, general financial conditions, and their collective impact on well-being in a time of considerable disruption.